Genetics patterns of inheritance (Geebung : Launchpad Multimedia, 1999)
Provides with a virtual laboratory in which they can perform a wide variety of self crosses, monohybrid crosses and dihybrid cross is not a game, but an invaluable experimental tool with many hours of activity
System requirements: Mac OS 7 or Windows 3.11 or Windows 95/98/NT, 256 colour, 14' monitor @ 640 X 480 resolution, 8 MB RAM, Quad speed CD-ROM drive, 8 bit sound card
Keywords: Genetics